Quantification of T4-Like and T7-Like Cyanophages Using the Polony Method Show They Are Significant Members of the Virioplankton in the North Pacific Subtropical Gyre - Goldin, Svetlana; Hulata, Yotam; Baran, Nava; Lindell, Debbie (Frontiers in Microbiology, 2020)
The North Pacific Subtropical Gyre (NPSG) is one of the largest biomes on Earth, with the cyanobacterium Prochlorococcus being the most abundant primary producer year-round. Viruses that infect cyanobacteria (cyanophages) influence cyanobacterial mortality, diversity and evolution. Two major cyanophage families are the T4-like cyanomyoviruses and T7-like cyanopodoviruses, yet their abundances and distribution patterns remain unknown due to difficulty in quantifying their populations. To address this limitation, we previously adapted the polony method (for PCR colony) to quantify T7-like cyanophages and applied it to spring populations in the Red Sea. Here, we further adapted the method for the quantification of T4-like cyanophages and analyzed the abundances of T4-like and T7-like cyanophage populations in the photic zone of the NPSG in summer 2015 and spring 2016. Combined, the peak abundances of these two cyanophage families reached 2.8 x 106 and 1.1 x 106 cyanophages·ml-1 in the summer and spring, respectively. They constituted between 3-16% of total virus-like particles (VLPs), comprising a substantial component of the virioplankton in the NPSG. While both cyanophage families were highly abundant, the T4-like cyanophages were generally 1.3-4.4 fold more so. In summer, cyanophages had similar and reproducible distribution patterns with depth. Abundances were relatively low in the upper mixed layer and increased to form a pronounced subsurface peak at 100 m (1.9 x 106 and 9.1 x 105 phages·ml-1 for the T4-like and T7-like cyanophages, respectively), coincident with the maximum in Prochlorococcus populations. Less vertical structure in cyanophage abundances was apparent in the spring profile, despite a subsurface peak in Prochlorococcus numbers. In the summer upper mixed layer, cyanophages constituted a smaller proportion of VLPs than below it and cyanophage to cyanobacteria ratios were considerably lower (1.3-2.8) than those of VLPs to bacteria (8.1-21.2). Differences in abundances between the two families and their contribution to VLPs with depth suggest differences in cyanophage production and/or decay processes relative to other members of the virioplankton in the upper mixed layer. These findings highlight the importance of quantifying distinct populations within the virioplankton to gain accurate understanding of their distribution patterns.